Possible Correlation between Hypomelanosis of Ito and Wilms' Tumor - Daniella Bello-Germino; Rasmey Chhin; Thu Tran; Tetyana L. Vasylyeva (Hindawi Limited, 2018)
Hypomelanosis of Ito is a neurocutaneous disorder characterized by skin manifestations in a characteristic pattern associated with musculoskeletal and central nervous system symptoms. Our patient was diagnosed with Wilms' tumor stage I at age two and was also found to have distinct streaked areas of skin hyper- and hypopigmentation suggestive of Hypomelanosis of Ito. We believe that our patient's clinical diagnoses of Hypomelanosis of Ito and Wilms' tumor are interlinked. The connecting factor is yet to be identified. Our patient does not have a deletion of 11p13 associated with a defect in WT1, the Wilms' tumor suppressor gene. As such, it is quite possible that what made her more susceptible to the development of Wilms' tumor was her Hypomelanosis of Ito, which is implicated in a number of other organ dysfunctions.